Prediksi Status Gizi Balita Menggunakan Logika Fuzzy Metode Sugeno Berdasarkan Pengukuran Antropometri - -, Safal; -, Findriyani; Rizal Adi Saputra (Jurnal Mahasiswa Teknik Informatika, 2024)
Under five nutritional status is a measure used to assess the nutritional level of children at an early age. In determining nutritional status using anthropometric measurements which involve physical measurements such as body weight and height. Then the threshold (Z-Score) is calculated and the nutritional status category of a child can be determined. this is of course more rigid because the measurement standards are firmer. Fuzzy logic allows for a more refined classification in determining nutritional status. In fuzzy logic, variables are not only limited to a few discrete categories such as thin, normal or fat. On the other hand, fuzzy logic introduces a continuous degree of membership which allows for a more refined classification based on the degree of membership in each category. This research is proven to produce predictions that are relatively correct, then testing has been carried out and it is proven from the test results that the application runs well.